Cost benefit analysis of current supply chain of LaFarge Holcim Bangladesh Limited - Tani, Tanzi Islam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.